Establishment of reference intervals for Platelet Function Analyzer -100 closure time in Algerian adults. - Malika Belkacemi; Yassine Merad; Mohamed Amine Merbouh (PLoS ONE)
Introduction The Platelet Function Analyzer-100 (PFA-100) is a point of care instrument that simulates plug formation under high shear flow. The PFA-100 measures the time required to occlude the aperture in a biochemically active cartridge and is expressed in a term of closure time (CT). In Algeria, the reference values used in clinical laboratories are of Western origin. However, ethnic, genetic, dietary environmental, and diet differences between populations may affect reference intervals. We established the reference intervals of PFA-100 closure times in healthy Algerian adults according to the International Federation of Clinical Chemistry method, and we compared them with those of Western and Asian countries. Material and methods We enrolled 303 healthy blood donors in the study. 218 subjects met inclusion criteria. We analyzed the blood sample on the PFA-100 for CT with both the collagen epinephrine and collagen ADP cartridges. Results The reference intervals of PFA-100 collagen epinephrine CT and PFA-100 collagen ADP CT were 91-207 seconds and 71-144 seconds, respectively. Compared to Western and Asian populations, there were significant differences. The upper limits of CTs were higher for Algerians in this study. Our findings show that many healthy Algerians would be incorrectly identified as having a primary hemostasis abnormality according to the reference intervals of the manufacturer and scientific literature. Conclusion This report provides the first reference intervals for PFA-100 CTs in healthy Algerian adults. These results improve the accuracy of diagnosis and patient care in Algeria.